Hachimijiogan, a traditional herbal medicine, modulates adipose cell function and ameliorates diet-induced obesity and insulin resistance in mice - Kagawa, Syota; Tanabe, Katsuya; Hiromura, Makoto; Ogawa, Kakuyou; Koga, Takayuki; Maeda, Takahiro; Amo-Shiinoki, Kikuko; Ochi, Hiroyuki; Ichiki, Yui; Fukuyama, Shogo; Suzuki, Saori; Suizu, Natsuki; et al. (Frontiers in Pharmacology, 2023)
Hachimijiogan (HJG) has originally been used to ameliorate a variety of symptoms associated with low ambient temperatures. However, its pharmacological action in metabolic organs remains unclear. We hypothesized that HJG may modulate metabolic function and have a potential therapeutic application to metabolic diseases. To test this hypothesis, we investigated metabolic action of HJG in mice. Male C57BL/6J mice chronically administered with HJG showed a reduction in adipocyte size with increased transcription of beige adipocyte-related genes in subcutaneous white adipose tissue. HJG-mixed high-fat diet (HFD)-fed mice showed alleviation of HFD-induced weight gain, adipocyte hypertrophy, liver steatosis with a significant reduction in circulating leptin and Fibroblast growth factor 21 despite no changes in food intake or oxygen consumption. Feeding an HJG-mixed HFD following four-weeks of HFD feeding, while a limited effect on body weight, improved insulin sensitivity with a reversal of decreased circulating adiponectin. In addition, HJG improved insulin sensitivity in the leptin-deficient mice without significant effects on body weight. Treatment with n-butanol soluble extracts of HJG potentiated transcription of Uncoupling protein 1 mediated by β3-adrenergic agonism in 3T3L1 adipocytes. These findings provide evidence that HJG modulates adipocyte function and may exert preventive or therapeutic effects against obesity and insulin resistance.